IMF Survey, Volume 35, Issue 15. (IMF Survey; IMF Survey ;, 2006)
IMF and low-income countries; De Rato in Tokyo; U.K. poverty initiative; Palau, Lithuania, Ethiopia, Kuwait; Volatility in Latin America; U.S. home equity withdrawal; Botswana: avoiding the resource curse; India: tax reform; U.S corporate cash balances.